Contrast Stretching Method for CMUcam 3 Camera and Histogram Equalization Method for Rocket Payload Ground Station - Bobi Kurniawan (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2013)
Abstract â€“ Refer to the theme â€œattitude monitoring and surveillance payloadâ€, KOMURINDO 2012 requires the participants to design a payload that can grab 200x200 greyscaled picture from the air then send it to LabVIEW ground station softwarein real-time (no buffer) to displayed. Sometime output image has bad quality for many reasons include sunlight intensityâ€™s too high or low and noises caused by data lost, therefore image enhancement contrast stretchingâ€™s implemented in payloadâ€™s microcontroller and histogram equalizationâ€™s implemented in ground station software. The main purpose of both algorithms is to distribute bit pixel value so that picture can be displayed more clear (contrast), median filter and average filter are also implemented in ground station in order to lighten noises. Output of those algorithms implementation leads transfer time for 1 picture in KOMURINDO 2012 format rule to 42,7- 43,1seconds. Distributed pixels value image is setted in range value 0 to 254 therefore image have good contrast. This means that objects in image can be seen easily.